A 10‐Year Portrait of Theorizing in Family Gerontology: Making the Mosaic Visible. Issue 2 (8th May 2020) - Humble, Áine M.; Seidel, Amber J.; Yorgason, Jeremy B.; Redden, Marco
Abstract : Based on a content analysis of family gerontology empirical studies in 13 journals (2009–2018), this article identifies theories currently being used and provides suggestions for future family gerontology theorizing. Family gerontologists are now using a greater range of theories than they were in the 1990s, including many middle‐range ones, and more scholars are citing multiple theories in their publications. Ways to advance family gerontology theorizing are to integrate more gerontology content into family theory textbooks, link middle‐range theories to broader general theories, and discuss how to use multiple theories effectively in research. Commonly used and emerging theories in family gerontology research can also be closely examined, and findings related to intersectionality and intergenerational ambivalence are briefly examined as examples of emerging theories used to study later‐life families.